Pengaruh Dukungan Selebriti dalam Komunikasi Politik Terhadap Sikap Pemilih pada Pemilihan Presiden 2024 - Dharta, Firdaus Yuni (Fakultas Ilmu Komunikasi Universitas dr. Soetomo, 2024)
Celebrity support for presidential candidates has become a common phenomenon in Indonesia. Celebrities with large followings on social media and high popularity can influence public opinion and voter attitudes. The internet and social media allow for political communication by celebrities. This research aims to analyze the influence of celebrity endorsement on voters' attitudes in the 2024 presidential election. This research uses quantitative methods with a survey approach. Data was collected through questionnaires distributed to respondents in Indonesia. The population of this study are voters in the 2024 presidential election. The sampling technique was carried out using random sampling technique. The collected data was analyzed using a regression test using the SPSS program. The research results show that celebrity endorsement can be one of the factors influencing voter attitudes in the 2024 presidential election. Celebrity endorsement can increase a candidate's popularity and influence public perception withpolitical communication of the candidate, especially among young voters, voters who have an emotional attachment to celebrities, and voters who are less have information about the candidate.